Cargo Transportation and Methylene Blue Degradation by Using Fuel‐Powered Micromotors - Zhonghao Li; Zhongzhou Xie; Hao Lu; Prof. Ying Wang; Yongsheng Liu (ChemistryOpen, 2021)
Abstract In the past two decades, micromotors have experienced rapid development, especially in environmental remediation, the biomedical field, and in cargo delivery. In this study micromotors have been synthesized from a variety of materials. Different functional layers and catalytic layers are formed through template electrodeposition (the bottom‐up method). At the same time, the article analyzes the influence of hydrogen peroxide concentration, surfactant type and concentration on the speed of the micromotors. Cargo transportation through tubular micromotors has always been a problem that people are eager to solve. In this article, we electrodeposit a layer of Ni in the microtubes, which effectively guides the microtubular motors to complete the cargo transportation. The potential applications of micromotors are also being explored. We added the prepared micromotors to the methylene blue solution to effectively enhance the degradation.